Link between Mediterranean diet and risk factors for acute coronary syndrome - Velicki, Radmila; Petrovic, Milovan; Bijelovic, Sanja; Bjelanovic, Jelena; Dragic, Natasa; Popovic, Milka; Velicki, Lazar (Progress in Nutrition, 2023)
Background and aim: A few studies have investigated the potential of the Mediterranean diet (MD) in secondary prevention of cardiovascular diseases (CVDs) and its possibility in alleviating the course and consequences of the diseases in a population following MD principles. The primary objectives of this study are to assess the level of adherence to the MD in patients with acute coronary syndrome (ACS) and in individuals at risk of developing CVDs, using a validated MedDiet score. Additionally, we aim to investigate whether the MD can play a protective role in reducing the occurrence and severity of ACS. Methods: The study examined 294 subjects, evenly split by gender, between the ages of 30 and 82, using an analytical cross-sectional method. Among all participants in the study the following examinations were conducted: anthropometric measurements, arterial blood pressure measurements, appropriate biochemical analysis, ECG and surveys using a specially prepared questionnaire, which included MedDiet score – validated score system for assessing the degree of compliance with MD pattern among subjects. Results: The study found that the mean MedDiet score of participants without ACS was significantly higher than that of participants with ACS (27.48 and 20.53 respectively, p=0.029). The MedDiet score was determined as an excellent marker for ACS with a cut-off value of 22.5, with a score of 22.5 or lower considered as an unfavorable result, and a score above 22.5 considered as a favorable result. The MedDiet score was found to have a negative correlation with systolic blood pressure, blood glucose values, serum triglyceride values and weak positive correlation with serum HDL values, atherosclerosis index and cardiac necrosis biomarker. Conclusions: Mediterranean diet has a protective effect on the incidence and severity of acute coronary syndrome in patients who are already ill and in those at a higher risk of developing cardiovascular disease.